Strategi Komunikasi Bisnis Mini Market Islam sebagai Pendidikan Kemandirian Santri: (Studi Kasus di Pondok Pesantren al-Barakah al-Nur Khumairoh Kabupaten Jember) - Nita Andriani (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2020)
In a conservative pondok pesantren's (Islamic boarding school) business, its management is run and only managed by the Kyai (An expert in Islam, the Head of the pesantren). However, such conservative management makes the business go slow in growth (passive), primitive and unsuitable with the needs of the growing market. Different from other conservative ones, the business of Pondok Pesantren Al-Barakah An-Nur Khumairoh, a convenient store, is not only for Kyai or his family's benefits, but for the Pondok Pesantren activities in general, major functions of the Pesantren, teachers' welfare, and others. The research data was obtained by interview, observation and documentation methods. The theory of communication employed in this research is Juli T. Wood's theory which states that there are three aspects that can benefit from learning communication: academic, professional, and personal aspects. Other theories employed are Interpersonal communication using a circular model and the Credibility theory, which consists of three: Initial Credibility, Derivative Credibility, and Terminal Credibility. The results of this study indicate that the acts of delegating, appointing and giving trust from a Kyai to the Santri to manage the business of a Pesantren - in this case the Convenience store of Pondok Pesantren al-Barakah an-Nur Khumairoh- is very effective in teaching independence to the santri. It can also instill entrepreneurial skill to the students.